2023
DOI: 10.3390/jtaer18030065
|View full text |Cite
|
Sign up to set email alerts
|

Social Commerce in Europe: A Literature Review and Implications for Researchers, Practitioners, and Policymakers

Abstract: The COVID-19 pandemic has altered consumer behavior, making social commerce a viable alternative throughout the world. Europe is trailing the US and China in adopting this technology, but the prognosis is encouraging. Our goal is to contribute to this process by offering a literature review on social commerce in Europe for researchers, practitioners, and policymakers. We analyzed 4.764 articles published during the 2015–2023 period on the topic of social commerce in Europe utilizing the PRISMA flow diagram. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…The study was conducted without specifying a timeframe, up to April 2023. Based on keyword searches and the inclusion and exclusion of the identified articles, 84 peer-reviewed research articles were identified that are published in international journals listed in electronic databases including ScienceDirect, Scopus, Emerald Insight, and Google Scholar from 2015 to April 2023 [19][20][21]. After that, an analysis of the geographic distribution of the published articles was used to address RQ2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted without specifying a timeframe, up to April 2023. Based on keyword searches and the inclusion and exclusion of the identified articles, 84 peer-reviewed research articles were identified that are published in international journals listed in electronic databases including ScienceDirect, Scopus, Emerald Insight, and Google Scholar from 2015 to April 2023 [19][20][21]. After that, an analysis of the geographic distribution of the published articles was used to address RQ2.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the assembling includes the identification of previous research on the acceptance of fintech app payment services from the consumer's perspective. This research focuses on peer-reviewed research articles published in international journals listed in electronic databases, including Sci-enceDirect, Scopus, Emerald Insight, and Google Scholar [19][20][21]. As examining fintech acceptance and adoption by consumers is recent, the first study was identified in 2015, with others following, up to April 2023.…”
Section: Assemblingmentioning
confidence: 99%